The Effect of Crystallization Time and Acid Type on the Synthesis of Nano-Gamma Alumina Using Double Hydrothermal Method - Mohammed, Abdul-Halim A.K.; Hussein, Hussein Q.; Mohammed, Mohammed Sabah (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Double hydrothermal method was used to prepare nano gamma alumina   using aluminum nitrate nano hydrate and sodium aluminate as an aluminum source, CTAB (cetyltrimethylammonium bromide) as surfactant, and variable acids: weak acids like; citric, and acitic acids, and strong acids like; hydrochloric and nitric acids as a bridge between aluminum salts and surfactant. Different crystallization times  12, 24, 48, and 72 hrs were applied. All the batches were prepared at pH equals to 9. XRD diffraction technique was used to investigate the crystalline nano gamma alumina pure from surfactant. N2 adsorption-desorption (BET) was used to measure the surface area and pore volume of the prepared nano alumina, the average particle size and the morphology of the surface of nano gamma alumina were estimated using AFM and SEM techniques, respectively. The sharpness of the peaks increased with increasing of crystallization time. The surface area, pore volume, and average particle size were decreased with increasing crystallization time. The best result of surface area was 383 m2/gm obtained using citric acid at 12 hr crystallization time, while the best results of pore volume and average particle size were 0.54cm3/gm and 72.37nm obtained using hydrochloric acid at12 hr crystallization time. Low agglomeration with hexagonal structure obtained using weak acids, while agglomeration occurred and clusters formed using strong acids.